Subclinical alcoholic optic neuritis without vitamin deficiency - Dally, S; Deplus, S; Delvert, S; Buisine, A; Hispard, E; Girre, C (Journal français d'ophtalmologie, 1985)
Vitamin B1, Folic acid Vitamin B12, whole blood Lead level, and plasma Zinc level were determined in 82 patients admitted to an alcoholism rehabilitation program. Each patient was examined for an optic neuritis. Thirty-two of the patients had sub-clinical abnormalities suggestive of optic neuritis like dyschromatopsias and/or field visual defects. No differences were found in the blood levels of Vitamin B1, Folic acid, and Vitamin B12 between the 32% affected and the 68% unaffected subjects. Moreover vitamins blood levels were found to be within the limits of normal values in both groups. A negative correlation between whole blood Lead levels and plasma Zinc levels was found. When an optic neuritis occurs the lead level tends to be higher and the Zinc lower. Abnormalities of the more usual alcoholism tests: gamma glutamyl Transpeptidase (gamma GT), mean red cell volume (V.G.M.) and glutamic Oxaloacetic transferase (T.G.O.), were more pronounced in alcoholics with optic neuritis.